Pilot Project Analysis of Seaplane Ecosystem Development in A Strategy to Improve Business Economy in The Selayar Islands, South Sulawesi: JEL Classification: R41, R58, L83, O18, Q56 - Muh Syaiful S; Sri Adrianti Muin; Abdul Samad Arief (Journal La Bisecoman, 2026)
Indonesia is the largest archipelago country in the world. It has over 17,000 islands, of which only around 7,000 are inhabite. For a country as diverse as Indonesia, needed good connectivity transportation is essential. Selayar Islands Regency is a regency that has the largest population in area South Sulawesi. Seaplanes are a means of transportation that can utilize the sea as a landing place and are expected to be able to meet the need for inter-island travel in Selayar Islands Regency. The final project of this thesis was carried out by modeling the SWOT analysis and capacity between seaplane transportation, then analyzed to create seaplane transportation for traveling between islands in the Selayar Islands region, especially the Takabonerate Marine Tourism Area. From the results of this research analysis, it can provide flight connectivity that can be utilized to improve the business economy in the Selayar Islands and South Sulawesi which do not have direct connections with islands that do not have airports, where seaplane transportation can save travel time significantly compared to using ship transportation.